Fentanyl decreases arterial blood oxygen saturation more than furanylfentanyl in mice due to increased apnea - Catherine Demery; Sierra C. Moore; Kelsey E. Kochan; Mengchu Li; Thomas D. Prince; Benjamin M. Clements; Zhongqi Chen; Jessica R. Whitaker-Fornek; Erica S. Levitt; Jessica P. Anand; John R. Traynor (Psychopharmacology, 2026)
Rationale Fatal opioid overdoses involving synthetic opioids have increased >10-fold over the past 8 years. Fentanyl, a potent synthetic opioid acting at the mu-opioid receptor (MOR), has largely replaced heroin as the predominant illicit opioid available. Various analogs have been synthesized from the fentanyl scaffold, including 2-furanylfentanyl, one of the most trafficked analogs from 2019 to 2024. Despite its prevalence, the in vivo effects of furanylfentanyl are not well characterized, especially regarding respiratory depression. Objectives To characterize furanylfentanyl relative to fentanyl in vitro and compare the effects of both drugs in mouse models of antinociception and respiratory depression. Methods The affinity and potency of fentanyl and furanylfentanyl were determined in CHO cells overexpressing MOR. Male and female CD-1 mice were administered ( i.p. ) fentanyl or furanylfentanyl prior to measuring antinociception (warm-water tail withdrawal), respiration (whole-body plethysmography), or oxygen saturation (pulse oximetry). Results Furanylfentanyl behaves as a partial agonist in vitro relative to fentanyl and morphine but with similar affinity and potency at MOR. In mice, fentanyl and furanylfentanyl produced similar effects on breathing parameters (including rate and inspiration time) that were greater than those induced by morphine, yet only fentanyl caused a drastic, long-lasting depletion of blood oxygen saturation. The discrepancy between effects on breathing and oxygen saturation may be explained by a greater number of apneas induced by fentanyl. Conclusions These results highlight the complexity of fentanyl-induced respiratory depression and indicate that recreational use of 2-furanylfentanyl in humans may pose a greater risk of overdose than morphine but lesser than fentanyl.